A study on job satisfaction among employees at TM Training Centre, Kuala Lumpur / Shamsina Hanapiah - Hanapiah, Shamsina (2009)
The objectives of this study are to determine the relationship between factors that can influence job satisfaction among employees at TM Training Centre, Kuala Lumpur as well as to measure the employees’ job satisfaction. Telekom Malaysia Training Centre (TM TC) was established by Telekom Malaysia Berhad (TM Berhad) as a training arm to provide training to their employees. Since TM Berhad had been restructured two times during 2008 which on April and December, TMTC also restructured. During the early stage of restructuring, employees seems to have difficulties to adapt with their new job role, new direct supervisor, and some new colleagues as the second restructuring occurs after several months. Job satisfaction has a positive relationship between employees’ performance as well as productivity in an organization. A total of thirty respondents were selected randomly among TM TC employees to answer structured questionnaires. The result of findings showed that the job descriptions and responsibilities/job tasks was a major factor in determining job satisfaction among employees at TM TC, Kuala Lumpur. It means that the work/job itself mostly influence employees’ job satisfaction. The other factors which are pay, supervision and the relationship with co-workers does not have any relationship with employees’ job satisfaction. However, most employees satisfied with the company and the jobs.